Decision aids linked to the recommendations in clinical practice guidelines: results of the acceptability of a decision aid for patients with generalized anxiety disorder - Ramos-García Vanesa; Perestelo-Pérez Lilisbeth; Rivero-Santana Amado; Peñate Castro Wenceslao; Duarte-Díaz Andrea; Álvarez-Pérez Yolanda; Martín-Trujillo María del Mar; Del Cura-González María Isabel; Serrano-Aguilar Pedro (BMC Medical Informatics and Decision Making, 2022)
Abstract Background Generalized anxiety disorder (GAD) is one of the most prevalent mental health problems. Patients with GAD have unmet needs related to the information received about their disorder, its treatments and their participation in the decision-making process. The aim of this study is to develop and assess the acceptability of a patient decision aid (PtDA) for patients with GAD. Method The PtDA was developed following the International Patient Decision Aid Standards. The recommendations of the Spanish clinical practice guideline (CPG) for patients with GAD were used as the basis. The first prototype was developed by an expert committee, further improvements were made with patients (n = 2), clinical experts (n = 13) and the project management group (n = 7). The acceptability of this second draft was assessed by patients non-involved in the previous phases (n = 11). Results The final PtDA version included a brief description of GAD and its treatments. Most participants agreed that the PtDA was easy to use, visually appealing and useful. At least half of the participants learned new things about treatments and adverse effects. Conclusions A PtDA was developed for patients with GAD based on recommendations from the Spanish CPG. It was improved and accepted by patients and clinical experts involved. An evaluation of its effectiveness on the shared decision-making process during the clinical encounter is planned.